Social Media Guidelines for Young Plastic Surgeons and Plastic Surgery Training Programs. Issue 2 (27th July 2021) - Hamilton, Kristy L.; Kim, Roy; Savetsky, Ira L.; Avashia, Yash J.; Maricevich, Renata; Rohrich, Rod J.
Abstract : Summary: Social media are a powerful tool that creates a unique opportunity for the young plastic surgeon and trainee to share content, brand oneself, educate the public, and develop one's own professional voice early. The majority of all plastic surgery programs and particularly those that are highly ranked have social media opportunities for their residents, yet clear rules to guide implementation of social media programming in residency have remained unspecified. These guidelines and pitfalls can be used to inform a productive and professional entry into plastic surgery social media use for the resident and young plastic surgeon. Details regarding specific platform use to maximize exposure are provided. The core principles of patient safety and privacy, authentic photography, plastic surgery education and advocacy, and professionalism inform these guidelines. Pitfalls include establishment of an online physician-patient relationship, engaging in debate by means of online reviews, providing medical entertainment, and engaging in non–plastic surgery politics. Use of these guidelines will allow the young plastic surgeon and trainee to succeed by means of social media platforms in an ethical and professional manner.